2013
DOI: 10.4103/2303-9027.117693
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis presenting as dysphagia: Clinical, endoscopic, radiological and endosonographic features

Abstract: Objective:Dysphagia as a presenting manifestation of tuberculosis is rare and there is paucity of data on the clinical, endoscopic and endosonographic features of these patients. We present our data related to the features over last four years.Methods:We analyzed retrospectively the clinical, endoscopic, radiological, endosonographic and cytological findings in 14 patients (male: 10; mean age: 37.7 ± 10.4 years) with dysphagia due to tuberculosis presenting to us over last 4 years.Results:Nine patients (64.3%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 12 publications
4
30
1
Order By: Relevance
“…In total, all of our patients had secondary involvement of esophagus. Most other reports also demonstrated that secondary TB is the most common type, with the most common mode of esophageal involvement secondary to mediastinal lymph nodal disease, and only one case series had predominant primary involvement of esophagus . In our study, the most common site of involvement was the mid‐esophagus, which correlated well with adjacent mediastinal lymphadenopathy.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…In total, all of our patients had secondary involvement of esophagus. Most other reports also demonstrated that secondary TB is the most common type, with the most common mode of esophageal involvement secondary to mediastinal lymph nodal disease, and only one case series had predominant primary involvement of esophagus . In our study, the most common site of involvement was the mid‐esophagus, which correlated well with adjacent mediastinal lymphadenopathy.…”
Section: Discussionsupporting
confidence: 74%
“…In comparison, the other two recent publications also reported median age of 31 and 37 years . Dysphagia is the most common symptom as mentioned in all publications, but uncommon presentation like hematemesis has also been reported in a few, and, in our series as well . Four of our patients also had fistula‐related symptoms.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Tuberculosis poses a challenge to healthcare professionals in its diagnosis and management. Esophageal tuberculosis is a form of extrapulmonary tuberculosis, which is rare [54]. …”
Section: Sarcoidosis and Tuberculosis Diagnosed By Eusmentioning
confidence: 99%